Design Analysis of Piezoelectric Cymbal Transducer (PCT) Array for Roadway Energy Harvesting System - Tuan Nurul Afiqah binti Tuan Putera; BC Kok (Evolution in Electrical and Electronic Engineering, 2021)
The shortage resources of non-renewable energy has leads to the invention of piezoelectric energy harvester. The piezoelectric energy harvester manages to convert the axle loading from travelling vehicles into useful electrical output where it can used for power up the street lamp or sensor. In this report, the array configurations of Piezoelectric Cymbal Transducer (PCT) with the conditioning circuit for roadway energy harvesting application is examined for its energy harvesting capabilities. Simulation studies using COMSOL FEA (Finite Element Analysis) simulation software has been carried out to find out the suitable array configurations of PCT that is capable to produce higher electrical output. The PCT design model comprises of eight PCT structures arranged in array configurations and placed in structural steel protective cover. A resistive load is connected in parallel with PCT model to examine the harvested power from the PCT. This study has found out that the array configurations with the utilisation of damper in various resistive load has significant corresponding effects on the power generation of PCT. A total generated power of 109 mW has been obtained from PCT array model with the utilisation of damper embedded in asphalt pavement under 30 kN load across 20 kΩ resistive load at frequency of 100 Hz. A conditioning circuit is designed to ensure the electric output is feasible to power up load such as street lamp. The conditioning circuit consist of rectifier, boost converter and energy storage is designed in Proteus Design Suite software. It has been discovered that the conditioning circuit managed to boost the input power to the output power by a ratio of 1:2. These results suggest that PCT array model with conditioning circuit managed to be implemented as energy harvester in roadway application.